Digital Marketing’s Influence on Gen Z’s Choice of Academic Institutions in Nepal - Kharel, Sameer (Nepalese Journal of Management Science and Research, 2025)
In today’s digital age, academic institutions in Nepal are increasingly active on social media platforms, often more so than on their official websites. This research evaluates the effectiveness of digital marketing strategies employed by Nepalese academic institutions in attracting Generation Z (Gen Z) students, who dominate the student population from secondary education to the PhD level. The study explores the relationship between academic institutions’ social media efforts and Gen Z students’ decision-making processes, focusing on the types of content that resonate most with this demographic. Additionally, the study examines the role of trust and credibility in digital marketing and identifies strategies that institutions can adopt to enhance their online presence. A survey of 152 Gen Z students, primarily from Kathmandu Valley, provides insights into their social media usage patterns, preferences, and perceptions of digital marketing content. The findings guide Nepalese academic institutions in refining their digital marketing strategies to better engage and attract Gen Z students